(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The study was conducted to describe the characteristics on the X-ray images of coal workers’ pneumoconiosis patients at a coal processing company. Method: A cross-sectional was conducted on 805 workers at the Coal and Port Joint Stock Company, Quang Ninh Province from January 2019 to October 2020. Results: 94.9% of subjects with coal workers’ pneumoconiosis exhibited small opacities (p/p), and 79% had opacities with a density ranging from 1/0 to 1/2. Conclusion: The characteristics observed on X-ray images of coal workers’ pneumoconiosis patients hold significant value and often manifest earlier than clinical symptoms. Therefore, workers exposed to coal dust should undergo regular occupational health examinations, including chest X-rays, for early detection of pneumoconiosis.